The Effects of Well-Being and Work Environment on Employee Loyalty and its Implications for Organizational Citizenship Behavior at Primasatya Husada Citra Hospital in Surabaya - Panca Herdy Prasetya; Taufik Zulfikar; Rulia Rulia; Vip Paramarta; Ayu Laili Rahmiyati (Green Publisher Indonesia, 2026)
Primastya Husada Citra Surabaya Hospital must have and retain employees who demonstrate loyalty and organizational citizenship behavior in creating safe and comfortable healthcare services as desired by almost all patients who come for treatment and enjoy the facilities available at Primastya Husada Citra Surabaya Hospital. This study aims to analyze the influence of employee well-being and work environment on employee loyalty, which in turn impacts organizational citizenship behavior at Primastya Husada Citra Surabaya Hospital. This study employed a quantitative method. After analyzing and describing the influence of employee well-being and work environment on employee loyalty through organizational citizenship behavior, based on the responses of 118 respondents selected as the sample in this study. Well-being has a significant positive effect on employee loyalty with a coefficient value of β = 0.441. The work environment has a positive and significant effect on employee loyalty with a path coefficient value of β = 0.521. Employee loyalty has a positive and significant effect on organizational citizenship behavior with a path coefficient value of β = 0.442. Loyalty has a positive and significant effect on organizational citizenship behavior with a path coefficient value of β = 0.978. Well-being has a positive and significant effect on organizational citizenship behavior with a path coefficient value of β = 0.429. Work environment has a positive and significant effect on organizational citizenship behavior with a path coefficient value of β = 0.429.